Construction of DNA ladder for determination of small size DNA fragments - Lan, Vo Thi Thuong; Thi Thanh, Le (Vietnam Journal of Biotechnology, 2021)
DNA marker is commonly used to determine the size of DNA fragments by electrophoresis in routine molecular biology laboratories. In this study, we report a new procedure to prepare recombinant plasmids pSY-60 which was partially digested by one restriction enzyme for generating DNA markers of 7 fragments from 60 to 420 bp. The procedure included a synthesis of 60 bp DNA fragment with EcoRI sites at both ends using PCR extension, self-ligation of the 60 bp fragments and subcloning the ligated product into plasmid, generating recombinant pSY-60. Once being cloned, 500 ng of 420 bp fragment purified from 100 µL PCR product was incompletely digested by EcoRI, sufficiently producing to 50 acrylamide gels. Our procedure for production of DNA markers could be simple, time saving and inexpensive in comparison with current ones widely used in most laboratories.